(3YbhO GdaQfTjR hCKQgG Ydi Mbhb GdedcjI GdUfGYjI hGdefGaSI GdMQI (B/ s - (3YGOd eMeO UahJ YHOGdQMef s; (3SGei YHOGdHGbi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3JJfGhd GdOQGSI eYGdLI ETcGdjI eROhLI jJYdb TbgG GdChd HHMK YdGbI YbhO GdaQfTjR HMbhb GdedcjI GdUfGYjI , TbgG GdKGfj jJeKd HhVY GdTQhW GdebjOI ddefGaSI GdhGQOI HYbhO GdaQfTjR(B: (3HESJYQGV GdbhGfjf hGdBQGA GdabgjI hGdCMcGe GdbVGFjI GdebGQfI HCf Mbhb GdedcjI GdUfGYjI oJYO eMdkG dYbhO GdaQfTjR hJejRg Yf ZjQg ef GdYbhO ,aVdkG Yf MXQ Jdc GdJTQjYGJ ddTQhW GdebjOI ddefGaSI (B: (3eY EecGfjg EYaGFgG ef GdMXQ ai MGdI KHhJ JMbjbgG dBKGQ eajOI ddEbJUGO GdhWfi Jahb CVQGQgG HGdefGaSI, MjK EfJgJ GdOQGSI HefGTOI GdeTQY GdeUQi dEbQGQ JTQjY dJfXje YbO GdaQfTjR s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2017s
(3HHdjhLQGajG(B: (3UaMGJ (B407-427s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3YbO GdaQfTR s; (3GdfXGe GdbGfhfi dYbO GdaQfTjR s; (3YdGbI YbO GdaQfTjR HMbhb GdedcjI GdUfGYjIs; (3GfbVGA YbO GdaQfTjRs; (3GdJcjja GdbGfhfi dYbhO GdaQfTjRs; (3GdTQhW GdYbOjI ai YbhO GdaQfTjRs; (3GdfXGe GdbGfhfi ddGYaGAs; (3fbd GdJcfhdhLjG s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs